Islamic Finance is Gaining Momentum Around the World - Moldabayev , Diyas (International Journal of Halal Research, 2023)
Most people still have little understanding and information about how Islamic banking system works. Misconceptions drive people to think that there is no real difference between Islamic banking and the traditional financial system. The root of the issue, in author’s humble opinion, simply lies with the fact that people don’t differentiate between such concepts as “riba” and “ribh” in terms of how they are formed. This article explains the essence and nature of the formation of these two concepts, while also presenting some insights that might serve as justifications for forbidding the practice of “riba” and gives a list of Shariah requirements for the most common Islamic finance product – Murabaha.